EFFECT OF CREAM FORTIFICATION BY FLAXSEED OIL (SOURCE OF OMEGA-3 FATTY ACIDS) IN SOME CHEMICAL, PHYSICAL AND SENSORY PROPERTIES - Mowafak M. Ali; SumayiaKh. Badawi; Shaymaa J. Mahmood (Mesopotamia Journal of Agriculture)
It has been manufactured CREAM rich in Omega-3 by fortification row cream 35% oil with Flax seed oil in the following fortification  rates (2.5, 5.5, 10.5%) and with tow treatments were made flax seed oil fortified with Vitamin E as an antioxidant , added to one of them , while the Vitamin E was not added to the other, at storage time(0, 4 ,8,12) day at temperature (5±1°c).Results showed that there was no significant differences in the sensory evaluation which conducted after processing directly in the characters color, flavor, texture and bitterness between the control cream and the cream treatments with fortification rates mentioned above, and for all kinds of cream which added in it antioxidant , and cream without adding antioxidant, mean while in the advanced period of storage a cream with fortification rate 10.5% which added in it Vitamin E  get the highest degree in sensory evaluation qualities mentioned above. There was significant reduction in the content of cholesterol in the cream and its directly proportional to the increase in the rate of fortification compared to the control cream. The development in the peroxide values and acid degree value during storage period was at least in cream with fortification rate of 10.5% which added in it Vitamin E and above was in the control treatment cream.Physical properties like as Melting point, Density and viscosity showed decrease in its values compared to the control cream. The quality and quantity test of fatty acids in control cream and cream treatments fortified with Flax seed oil by GLC appeared that had been increased of poly unsaturated fatty acids (α- Linolenic Acid) in cream treatments which fortified as a result to the fortification by Flax seed oil.